Effectiveness of Blue Light Patrol in Handling Increased Use of Brong Exhaust to Guarantee Harkamtibmas at the Madiun City Police - Pinaya, Arya Digit Rusadi (Police Studies Review, 2024)
This research discusses the effectiveness of blue light patrols in dealing with increases the use of Brong exhaust to maintain law and order and law and order at the Madiun City Police Station. Purpose of the research This is a description and analysis of the implementation of the Samapta unit’s blue light patrol Madiun City Police and what factors influence the handling of exhaust use Brong uses blue light patrols. Discussion regarding the implementation of blue light patrols carried out by members of the Samapta Patrol Unit in dealing with the increase in Brong exhaust users This study uses a descriptive research approach with a research focus on the implementation of blue patrols light by members of the Samapta Unit patrol in handling the recruitment of brong exhaust users. Next, to obtain data, the author uses primary data sources and data sources secondary. For primary data sources, obtained by means of interviews and observations, while secondary resources are obtained through document study. Based on findings in In this research, the use of Brong exhaust is one of the highest motor vehicle violations things that disturb public security and law and order in the Madiun City area. Not yet in the implementation of the patrol fully comply with procedures. Implementation of patrols that can support and hinder including human resources, facilities and infrastructure, budget and society. Conclusion obtained in this research is based on the strategic location of the Madiun City area for implementation of illegal racing using Brong exhaust. In practice, patrols are not appropriate procedures and there are several factors that influence the less than optimal implementation of blue patrols light.